Effect of Tea Polyphenols on the Oxidation and Color Stability of Porcine Hemoglobin. Issue 8 (11th July 2019) - Dong, Jingwen; Zhou, Yaoqing; Lu, Yunhao; Lv, Yuanping; Chi, Yuanlong; He, Qiang
Abstract : Abstract: The oxidation and color stability of porcine hemoglobin (Hb) in the presence of tea polyphenols (TP), as well as the mechanism, were investigated using the methods of color and oxidation analyses, ultraviolet‐visible and fluorescence spectroscopy. Results indicated that TP interacted with the tryptophan and tyrosine residues of Hb through inserting into its hydrophobic pocket. This interaction showed a concentration‐dependent effect on Hb, which might lead to completely opposite results. The presence of TP (16 mg/L) disrupted Hb (16 mg/L) structure, and the exposure of heme iron facilitated the oxidation and discoloration of Hb. However, a lower level of TP should not break Hb structure but could work as an antioxidant and restrain the formation of methemoglobin. Consequently, TP (1.6 mg/L) considerably maintained the redness of Hb (16 mg/L, P < 0.05) when stored at pH 7.4 and 25 °C for 72 hr. Results may provide scientific information for the proper use of TP in blood and meat products. Practical Application: Proper utilization of tea polyphenols (TP) in food products is beneficial to improve antioxidant capacity and nutrition quality of food. We proved that it was potential to corporate TP into blood and meat products to prevent discoloration and oxidative deterioration.